ПЕРСПЕКТИВИ РОЗВИТКУ РЕСТОРАННОГО БІЗНЕСУ ЯК ОДНІЄЇ ЗІ СКЛАДОВИХ ЛАНОК ГОСТИННОЇ ІНДУСТРІЇ - Hritsenko, O.M. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2009)
The article describes the present situation in the restaurant industry, determines perspective trends in the development of restaurant facilities and analyses the development of restaurant business in Ukraine and Khmelnytsk region.